2022
DOI: 10.1021/acsnano.2c02928
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Skyrmionic Bubbles at Room Temperature and Sign Reversal of the Topological Hall Effect in a Layered Ferromagnet Cr0.87Te

Abstract: The search for materials that exhibit topologically protected spin configurations, such as magnetic skyrmions, continues to be fueled by the promise of outstanding candidate components for spin-based applications. In this study, in situ Lorentz transmission electron microscopy directly images Bloch-type magnetic skyrmionic bubbles in a layered ferromagnet Cr0.87Te single crystal. Owing to the competition between a magnetic dipole interaction and uniaxial easy axis anisotropy, nanoscale magnetic bubbles with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
(68 reference statements)
2
18
0
Order By: Relevance
“…The magnetic domain structure at 2 K was a maze-like domain, while the domain structure at 90 K shows that several small magnetic bubbles with dark contrast appear within the large domain with bright contrast, and the diameter of each magnetic bubble is approximately 500 nm, which may be skyrmions. It was also discovered recently in other chromium-based tellurides such as Cr 1+δ Te 2 (δ ≈ 0.3), Cr 3 Te 4 , and Cr 0.87 Te . Furthermore, we observed the evolution of the magnetic bubbles with an external magnetic field.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The magnetic domain structure at 2 K was a maze-like domain, while the domain structure at 90 K shows that several small magnetic bubbles with dark contrast appear within the large domain with bright contrast, and the diameter of each magnetic bubble is approximately 500 nm, which may be skyrmions. It was also discovered recently in other chromium-based tellurides such as Cr 1+δ Te 2 (δ ≈ 0.3), Cr 3 Te 4 , and Cr 0.87 Te . Furthermore, we observed the evolution of the magnetic bubbles with an external magnetic field.…”
Section: Resultssupporting
confidence: 80%
“…With an upward additional magnetic field vertically to the ab -plane applied to the nanosheet, we found that when the value of the additional magnetic field was within the range of 0–70 mT, the magnetic bubbles existed stably. Based on their stability, we think that the magnetic bubbles are probably skyrmions. As the additional magnetic field increased to 80 mT, the two magnetic bubbles in the center merge together. When the additional magnetic field is increased to 90 mT, the dark domain expands to cover most of the region of the Cr 5 Te 8 nanosheet, and a new inverse magnetic bubble is formed in the dark domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of creation, annihilation, and motion of magnetic skyrmions offers interesting perspectives for both fundamental physics , and potential applications in information processing. , Among the materials hosting skyrmions, ferrimagnetic alloys or exchange coupled rare-earth/transition-metal (RE/TM) multilayers have attracted a lot of attention because of the ability to sustain the zero-field skyrmions as well as the potential of avoiding the skyrmion Hall effect. For instance, Cezar and co-workers succeeded in observing the sub-100 nm skyrmions in nanostructured ferrimagnetic Pt/CoGd/Pt discs without any help of magnetic field, which is highly desirable for skyrmionic applications such as magnetic tunnel junctions and nano-oscillators.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been great interest in the burgeoning low-dimensional ferromagnetic materials, [25][26][27] such as the chromium telluride (Cr x Te y ) family, [28][29][30][31][32][33][34] Cr 2 Ge 2 Te 6 , [35] Fe 3 GeTe 2 , [36] Fe 5 GeTe 2 , [37] Fe 3 GaTe 2 , [38] and CuCr 2 Te 4 , [39] owing to their intrinsic high-temperature ferromagnetism for versatile applications. [40] The emergent THE has been notably found in these low-dimensional ferromagnetic systems, including their heterostructures (e.g., CrTe/SrTiO 3 , [41] Cr 2 Te 3 /Bi 2 Te 3 , [42] Fe 3 GeTe 2 /WTe 2 , [43] CrTe 2 /Bi 2 Te 3 , [44] and Cr 2 Te 3 /Cr 2 Se 3 [45] ), bulk forms (e.g., Cr 5 Te 8 , [46] Cr 0.9 B 0.1 Te, [47] Cr 0.87 Te, [48] and Cr 1. 53 Te 2 [49] ), nanosheets (e.g., Cr 5 Si 3 [50] ), and exfoliated nanoflakes (e.g., Cr 1.2 Te 2 [51] ), demonstrating their potential applications in chiral spintronics.…”
Section: Introductionmentioning
confidence: 99%